Experience the Difficulty of Caregivers in Caring for Infant with Chronic Lung Disease at Home - ชมพิกุล, เรณู; จีระแพทย์, วีณา (Journal of The Royal Thai Army Nurses, 2019)
This qualitative study was to describe the phenomena of difficulty of family caregivers in caring for infants with chronic lung disease (CLD). Informants were 14 family caregivers who were taking care of infants with CLD no more than two years after hospital discharge. Data were collected by in-depth interviews and audio recording. Colaizzi approach analysis was used to analyze data in this study. Findings revealed experience the difficulty of caregivers in caring for infant with CLD at home in order to comply with the infant’s treatment plan, prevention of complications and health recovering could be categorized into 7 major themes: 1) punctual administration of multiple medications 2) close monitoring of respiratory signs and symptom, 3) seeking ways to help infants with constipation, 4) finding a way to feed the infants and to alleviate vomiting, 5) searching all possible ways for the child/grandchild to gain weight, 6) feeling helplessness when the child became tired and cyanotic and 7) experiencing high costs of care This study generated insights into the complex tasks, emotions, and coping of caregivers caring for infants with CLD. The nurses can take information used in developing the discharge planning can preparation for caregivers’ ability to handle the infants’ health problems at home and decrease rate readmission in hospital.